Sārānukrom klum chāttiphan nai Prathēt Thai : Čhīn H̨̄o - N̨̄orasēt Phisitphanph̨̄on (Sathāban Wičhai Phāsā læ Watthanatham ph̄ưa Phatthanā Chonnabot, Mahāwitthayalai Mahidon, 2005)
Encyclopedia of Chin Ho ethnic group in Thailand.